2020
DOI: 10.1186/s12885-020-06844-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nuclear YAP1 expression in residual cancer after neoadjuvant chemohormonal therapy with docetaxel for high-risk localized prostate cancer

Abstract: Background: Although docetaxel-based chemohormonal therapy (CHT) is one of the standard treatments for castration-resistant prostate cancer (CRPC), pertinent biomarkers and precise mechanisms involved in the resistance for CHT for CRPC remain unknown. We investigated the relationship between chemohormonal resistance and the expression of steroid receptors and Hippo pathway proteins using a docetaxel-resistant prostate cancer (PCa) cell line and human PCa tissues in patients who underwent surgery with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…YAP overexpression or increased activity may predict advanced tumour stages and poor clinical outcome in cancer patients 25,85,92 . A more recent discovery indicated that expression of nuclear YAP (nYAP) was noticeably upregulated in docetaxel‐resistant prostate cancer cell lines than parental cells 93 . Consistently, clinical data also revealed a higher nYAP level in the chemohormonal therapy (CHT) group than other groups, and patients with overexpressed nYAP in residual cancer after CHT predicted higher biochemical recurrence, indicating that nYAP level may be a promising prognostic factor in castration‐resistant prostate cancer patient treated with CHT 93 .…”
Section: The Clinical Significance Of Lncrnas Involved In Hippo Pathwmentioning
confidence: 99%
See 1 more Smart Citation
“…YAP overexpression or increased activity may predict advanced tumour stages and poor clinical outcome in cancer patients 25,85,92 . A more recent discovery indicated that expression of nuclear YAP (nYAP) was noticeably upregulated in docetaxel‐resistant prostate cancer cell lines than parental cells 93 . Consistently, clinical data also revealed a higher nYAP level in the chemohormonal therapy (CHT) group than other groups, and patients with overexpressed nYAP in residual cancer after CHT predicted higher biochemical recurrence, indicating that nYAP level may be a promising prognostic factor in castration‐resistant prostate cancer patient treated with CHT 93 .…”
Section: The Clinical Significance Of Lncrnas Involved In Hippo Pathwmentioning
confidence: 99%
“…A more recent discovery indicated that expression of nuclear YAP (nYAP) was noticeably upregulated in docetaxel‐resistant prostate cancer cell lines than parental cells 93 . Consistently, clinical data also revealed a higher nYAP level in the chemohormonal therapy (CHT) group than other groups, and patients with overexpressed nYAP in residual cancer after CHT predicted higher biochemical recurrence, indicating that nYAP level may be a promising prognostic factor in castration‐resistant prostate cancer patient treated with CHT 93 . Furthermore, in conventional osteosarcoma, YAP/TAZ immune‐reactive score was significantly correlated with the overall survival (OS), and its nuclear expression was associated with progression‐free survival, 94 suggesting a prominent link between YAP/TAZ expression and osteosarcoma prognosis.…”
Section: The Clinical Significance Of Lncrnas Involved In Hippo Pathwmentioning
confidence: 99%
“…When the Hippo signaling pathway is activated, MST1 induces YAP phosphorylation in the presence of associated scaffolding proteins. When phosphorylated YAP accumulates in the cytoplasm, it is rapidly degraded by ubiquitination, thus exerting its effect of inducing apoptosis and inhibiting cell proliferation (15)(16)(17). Wang et al found that FFAR1 and FFAR4-dependent Hippo pathway activation mediated DHA-induced apoptosis in androgen non-dependent prostate cancer cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic change of PCa after NCHT was not a significant factor of bPFS and OS in our study. Although previous report also demonstrated pathologic change of PCa after NCHT did not affect bPFS [ 12 ], further investigation of pathologic features of NCHT species could elucidate molecular target to predict the NCHT resistance [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%